FGL2 deficiency alleviates maternal inflammation-induced blood-brain barrier damage by blocking PI3K/NF-κB mediated endothelial oxidative stress - Huang, Lianjing; Zhan, Di; Xing, Ying; Yan, Yaqin; Li, Qing; Zhang, Jingyi; Li, Sujuan; Ning, Qin; Zhang, Cai; Luo, Xiaoping (Frontiers in Immunology, 2023)
Introduction: The impairment of blood-brain barrier (BBB) is one of the key contributors to maternal inflammation induced brain damage in offspring. Our previous studies showed Fibrinogen-like protein 2 (FGL2) deficiency alleviated maternal inflammation induced perinatal brain damage. However, its role in BBB remains undefined. Methods: Lipopolysaccharide (LPS) was intraperitoneally injected to dams at Embryonic day 17 to establish maternal inflammation model. FGL2 knockout mice and primary brain microvascular endothelial cells (BMECs) were used for the in-vivo and in-vitro experiments. BBB integrity was assessed by sodium fluorescein extravasation and tight junction (TJ) protein expression. Oxidative stress and the activation of PI3K/NF-κB pathway were evaluated to explore the mechanisms underlying. Results: Upon maternal inflammation, BBB integrity was remarkedly reduced in neonatal mice. Meanwhile, FGL2 expression was consistently increased in BBB-impaired brain as well as in LPS-treated BMECs. Moreover, FGL2 deficiency attenuated the hyperpermeability of BBB, prevented the decline of TJ proteins, and reduced the cytokine expressions in LPS-exposed pups. Mechanistically, the indicators of oxidative stress, as well as the activation of PI3K/NF-κB pathway, were upregulated after LPS exposure in vivo and in vitro. FGL2 deletion decreased the generation of ROS and NO, reduced the endothelial iNOS and NOX2 expressions, and suppressed the PI3K/NF-κB pathway activation. Besides, inhibition of PI3K by LY294002 decreased the oxidative stress in LPS-treated wild type BMECs. While, overexpression of PI3K by lentivirus reemerged the induction of NOX2 and iNOS as well as NF-κB activation in FGL2-deleted BMECs. Conclusion: Our findings indicate that FGL2 deficiency alleviates the maternal inflammation-induced BBB disruption by inhibiting PI3K/NF-κB mediated oxidative stress in BMECs. Targeting FGL2 may provide a new therapy for prenatal brain damage of offspring.